Strategic Change: Strategic Change Indicators - Practical Approach - Jan Makary FRYCZAK (Communications of International Proceedings, 2021)
Strategic change is a research topic of significant interest in the management literature. Therefore, researchers need tools to detect strategic changes in enterprises. There exists a set of financial ratios used as indicators of strategic change that have been used consistently for almost 50 years. This study aims to test their current usefulness in the context of electronic financial statements published in the XBRL format in the USA. Using a data from the US Securities and Exchange Commission, the study shows low availability of strategic change indicators in the data set. Only two financial ratios are widely available: inventory levels and equipment depreciation. The study offers implications for researchers who would like to plan research based on machine-readable company data.
Keywords: Strategic Change; Strategic Management; XBRL